IN SITU IRON ISOTOPE RATIO DETERMINATION USING UV-FEMTOSECOND LASER ABLATION WITH APPLICATION TO HYDROTHERMAL ORE FORMATION PROCESSES - Horn I.; von Blanckenburg F.; Schoenberg R.; Steinhoefel G.; Markl G. (My University, 2006)
The feasibility of in situ stable Fe isotope ratio measurements using UV-femtosecond laser ablation connected to a multiple-collector inductively coupled plasma mass spectrometer (MC-ICP-MS) has been investigated. Different types of matrices, independently determined by solution MC-ICP-MS after chromatographic separation of Fe, have been analysed by laser ablation using the isotopically certified iron reference material IRMM-014 as the bracketing standard. The samples have been pure iron metal (JM Puratronic), Fe-meteorites (North Chile, Glenormiston and Toluca), the meteorite phases kamacite and taenite in Toluca and Fe-sulphides. Furthermore, Fe isotope ratios from hydrothermal hematite, siderite and goethite from an old mining area in the Schwarzwald, Germany, and of magnetite from the metamorphic Biwabik iron formation have been determined. The results show that a precision of better than 0.1‰ (2 sigma) can be achieved with laser ablation and that all the results obtained agree with those determined by solution ICP to better than 0.1‰. This precision and accuracy is achievable in both raster and spot ablation mode. A matrix-matched bracketing standard is not required, and all these materials can be measured accurately against a metal standard. The hydrothermal minerals show significant Fe isotope zonations. In some samples the range of δ56Fe in a single aggregate encompasses the entire spectrum of ratios found by bulk solution analyses in multiple samples distributed over the whole mining district. For example, isotopic zonations found in secondary fibrous hematites show a continuous change in the δ56Fe values from -0.5‰ in the core to -1.8‰ in the rim. Primary hydrothermal siderite shows the reverse pattern with lighter values in the core than in the rim. While the siderite is thought to record primary fluid histories, the hematite pattern is interpreted as a reworked isotopic signature generated by oxic dissolution of primary zoned siderite and immediate close range re-precipitation of the oxidized Fe. Abrupt changes are documented for secondary goethite showing a distinct overgrowth that is 0.4‰ lighter than the core of the grain. If indeed Fe isotopes in secondary minerals from hydrothermal ore deposits record the initial isotopic signatures of their precursor minerals, and these in turn record hydrothermal fluid histories, then the tools are in place for a detailed reconstruction of the deposit's genesis. We expect similar observations from other Fe-rich deposits formed at intermediate and low-temperatures (e.g. banded iron formations). Laser ablation now provides us with the spatial resolution that adds a further dimension to our interpretation of stable Fe-isotope fractionation. © 2006 Elsevier Inc. All rights reserved.